Motion Analysis of Core Stabilization Exercise in Women: Kinematics and Electromyographic Analysis - Kyeongjin Lee (Sports, 2023)
As core stabilization exercise is essential for maintaining a stable spine and improving functional performance, understanding the activation of core muscles and the stabilization of the trunk and pelvis during such exercise is crucial. The purpose of this study was to investigate the muscle activation and stabilization of the lumbar–pelvic region during core stabilization exercise, with a specific focus on analyzing EMG and 3D motion kinematic data. The study aimed to understand how different tension settings on the reformer affect muscle activation and hip motion, as well as how these factors impact pelvic and trunk stability during the exercise. The reformer consists of a carriage that slides back and forth on rails, with springs providing resistance. The springs can be adjusted to vary the resistance level. Twenty-eight healthy women participating in this study were asked to perform ‘side splits’, a hip abduction exercise, on the reformer in both heavy and light tension settings. Activation of the internal oblique (IO), rectus abdominis (RA), multifidus (MU), costal lumbosacral (IL), gluteus medius (GM), and adductor muscles (AL) were measured using electromyography (EMG) and 3D motion. Kinematic data using an assay were also measured during exercise. GM, IO, and MU muscles were more active when heavy springs were used, and AL muscles were more active when light springs were used. Hip motion was more symmetrical when lighter springs were used with a greater range of hip motion. There was less pelvis and torso weight transfer and more torso and pelvis stability when the heavier springs were used. In this study, we confirmed that core stabilization exercise on an unstable surface activates the deep muscles of the abdomen and back and is effective for pelvic and trunk stabilization training.